Vector control interventions for visceral leishmaniasis elimination initiative in South Asia, 2005-2010 - Picado, Albert (Medknow Publications & Media Pvt Ltd, 2012)
The Visceral Leishmaniasis (VL) Elimination Initiative in the Indian subcontinent was launched in 2005 as a joint effort between the governments in the Region (India, Nepal and Bangladesh) and the World Health Organization (WHO). The objective is to reduce the annual VL incidence below 1/10,000 inhabitants by 2015 based on detection and treatment of VL cases and vector control. We present here a review of studies published in the period 2005-2010 on the efficacy of different tools to control Phlebotomus argentipes. The review indicates that the current indoor residual spraying (IRS) and novel vector control methods mainly insecticide treated nets (ITN) have low effectiveness for several reasons. Efforts to improve quality of IRS operations and further research on alternative and integrated vector control methods need to be promoted to reach the VL elimination target by 2015.